In Vitro Study of Action Mode of Rhodotorula minuta Dmg 16 BEP as Biocontrol Agents on Alternaria solani - Wawan Setiawan; Suryo Wiyono; Efi Toding Tondok; Atit Kanti; I Made Sudiana (Jurnal Perlindungan Tanaman Indonesia, 2020)
Rhodotorula sp. is widely known as a biocontrol agent and is reported effective in controlling several diseases on crops. Rhodotorula minuta Dmg 16 BEP is an antagonist yeast from Indonesia which was effective in controlling various plant diseases. The objective of this research was to study the in vitro mode of action of R. minuta Dmg 16 BEP against Alternaria solani. The antibiosis ability of R. minuta Dmg 16 BEP to A. solani might be based on the activity of volatile compounds and not from its metabolites products. The growth of A. solani in paper disk assay and dual culture tests were not inhibited nor inhibitory zones  developed, whereas the inverse petridish test showed the growth inhibition of A. solani. The results of the chitinolytic activity test on chitin agar and proteolytic on skim milk agar showed that no clear zone was formed. R. minuta has a strong hyperparasitic ability according to the slide culture test as the yeast cells surrounded A. solani hyphae and caused damage to some parts of hyphae.